Mission Difficult…but Not Impossible Making Public-Private Partnerships Work for the Poor - Taylor, Robert (World Bank, Washington, DC, 2012)
Public-private partnerships (PPPs) hold great promise for improving public services for the poor in emerging markets. But charting the political waters, balancing the needs of governments, consumers, investors, and lenders, and making the transaction transparent and sustainable are challenging tasks and not for the faint of heart. This smart lesson summarizes 10 years of lessons of International Finance Corporation's (IFC's) Infrastructure Advisory Department in its role as transaction advisor to governments on more than 100 mandates.